PELATIHAN TERNAK KAMBING DI DESA KAHINGAI KECAMATAN BELANTIKAN RAYA KABUPATEN LAMANDAU - Pujiastuti, Asih (Jurnal Abdi Insani, 2025)
Farmers in Kahingai Village still raise goats traditionally, although they have begun to apply several principles of intensive management. One of the main problems faced by goat farmers is the availability of feed, especially during the dry season. Farmers have difficulty obtaining sufficient and quality feed so that livestock are only given makeshift feed. To overcome this, it is necessary to apply feed technology (silage) as an effort to ensure the availability of feed, especially during the dry season. The purpose of this community service activity is to improve the understanding and skills of farmers in raising livestock. In addition, it is also expected that there will be an increase in livestock production by utilizing local feed resources. The methods of activities carried out include socialization, counseling and training. The socialization of the program begins with holding meetings with the community/farmers to schedule activities and materials to be implemented, then counseling is carried out through lectures and discussions and participatory methods, namely involving farmers directly in feed processing training. The result of this activity is that farmers in Kahingai Village have succeeded in making good quality silage. The characteristics of the silage produced are brownish green, free of mold, do not clump and have a distinctive fermentation aroma. The success of making silage indicates that the fermentation process is running optimally. Success also shows that the training provided can be absorbed and has the potential to be applied for sustainability at the farmer level. In addition, the enthusiasm of farmers during the activity shows that farmers are interested in adopting the feed technology that has been introduced. Community service activities in Kahingai Village increase farmers' knowledge regarding good and correct maintenance management. Community service activities can also increase farmers' understanding in making silage.